Is There an Increased Risk of Tumor Recurrence When Intraoperative Blood Salvage Autotransfusion Used for Liver Transplantation in Patients with Hepatocellular Carcinoma? - Akbulut, Sami; Kayaalp, Cuneyt; Yilmaz, Mehmet; Ozgor, Dincer; Karabulut, Koray; Eris, Cengiz; Toprak, Huseyin Ilksen (Wiley-Blackwell, 2012)
[Abstract Not Available]
18th Annual International Congress on ILTS -- MAY 16-19, 2012 -- San Francisco, CA